Characterization of morphological and chemical changes using atomic force microscopy and metabolism assays: the relationship between surface wax and skin greasiness in apple fruit - Yang, Yanqing; Xie, Xiucui; Huang, Rong; Yan, Kemeng; Wang, Mengdi; Liu, Wenjing; Zeng, Xiangquan; Ren, Xiaolin; Gong, Hansheng (Frontiers in Plant Science, 2024)
Skin greasiness occurred on stored apples (Malus domestica Borkh.) is generally believed to result from changes in surface wax components. Previous reports have typically correlated wax changes with greasiness scores, a sensory index used to evaluate skin quality but influenced by individual perception. This study aimed to assess skin quality by quantitatively analyzing wax morphology changes in greasy 'Jonagold' apples using Atomic Force Microscopy (AFM) roughness parameters Ra, Rq, Rmax, and Rz, and to correlate these changes with wax composition. AFM results revealed that wax crystals disappeared as skin greasiness increased, accompanied by significant declines in roughness parameters Ra, Rq, Rmax, and Rz, which decreased by 70% to 85%. Chemical analysis showed a significant increase in liquid esters, including linoleate and oleate esters, in the surface waxes, which negatively correlated with the decline in roughness parameters. Key genes related to ester production, such as MdFAD2, MdWSD1, and MdWBC11, exhibited increased expression and were also negatively correlated with decreases in Rq, Ra and Rz. Additionally, 1-Methylcyclopropene (1-MCP) treatment suppressed both the development of greasiness and the associated changes. Our findings suggest that the increased liquid esters contribute to alternations in wax morphology in greasy apples, and that MdFAD2, MdWSD1, and MdWBC11, play crucial roles in ester biosynthesis. These results highlight the effectiveness of AFM roughness parameters Ra, Rq, Rmax, and Rz in quantifying wax morphology changes in apples during skin greasiness development.